Selection of an Endophytic Streptomyces sp. Strain DEF09 From Wheat Roots as a Biocontrol Agent Against Fusarium graminearum - Colombo, Elena Maria; Kunova, Andrea; Pizzatti, Cristina; Saracchi, Marco; Cortesi, Paolo; Pasquali, Matias (Frontiers in Microbiology, 2019)
Selection of biological control agents (BCA) profits from an integrated study of the tripartite interactions occurring among the BCA, the plant and the pathogen. The environment plays a crucial role in the efficacy of BCA, therefore, the selection process shall utmost mimic naturally occurring conditions. To identify effective biocontrol strains against Fusarium graminearum, the major cause of Fusarium head blight (FHB) in wheat and deoxynivalenol (DON) accumulation in grains, a workflow consisting of in vitro and in vivo assays was set up. Twenty-one Streptomyces strains, 16 of which were endophytes of different plants, were analyzed. In vitro and in vivo tests characterized their plant growth promoting (PGP) traits. Biocontrol activity against F. graminearum was firstly assessed with a dual culture assay. An in vivo germination blotter assay measured Fusarium foot rot and root rot symptoms (FFR-FRR) reduction as well as growth parameters of the plant treated with the Streptomyces strains. A selected subset of Streptomyces spp. strains was then assessed in a growth chamber measuring FFR symptoms and growth parameters of the wheat plant. The approach led to the identification of an effective Streptomyces sp. strain, DEF09, able to inhibit FHB on wheat in controlled conditions by blocking the spread of the pathogen at the infection site. The results were further confirmed in field conditions on both bread and durum wheat, where DEF09 decreased disease severity up to 60%. This work confirms that FRR and FFR pathosystems can be used to identify BCA effective against FHB.